Proven Invasive Fungal Infections in Pediatric Hemato-Oncologic Patients: Clinical Characteristics and Epidemiological Challenges - Marcela Lizeth Morales López; Denisse Natalie Vaquera Aparicio; José Iván Castillo Bejarano; Abiel Homero Mascareñas de los Santos; Rogelio de Jesús Treviño Rangel; Paul Santiago Arcos Viscarra; Ana Sofia Guerrero Delgado (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background Invasive fungal infections (IFIs) represent a major cause of morbidity and mortality in pediatric hemato-oncologic patients, particularly during periods of profound immunosuppression. Although Candida spp. and Aspergillus spp. remain the most frequently identified pathogens, recent reports have shown an expanding spectrum of emerging molds. Despite improvements in diagnostic tools and antifungal therapy, delays in recognition and initiation of treatment continue to contribute to unfavorable clinical outcomes. Evidence from Latin America remains limited, restricting understanding of regional epidemiology and clinical behavior. This study aimed to describe the epidemiological profile and clinical characteristics of proven IFIs in pediatric hemato-oncologic patients managed at a tertiary-care center. Methods We conducted an observational, retrospective, descriptive, cross-sectional study through review of medical records from pediatric patients diagnosed with proven IFIs according to the 2020 European Organization for Research and Treatment of Cancer and Mycoses Study Group (EORTC/MSGERC) criteria. The study was performed at Hospital Universitario “Dr. José Eleuterio González” in northeastern Mexico and included cases identified between 2018 and 2024. Descriptive statistics were calculated, and Chi-square, Fisher’s exact test, and Student’s t-test were used for comparisons. A multivariable logistic regression analysis was performed to identify independent predictors of mortality. Statistical analyses were completed using SPSS version 25.0. Results Thirty-three patients were included; 54.5% were male, with a mean age of six years. Most patients (91%) were classified as high-risk for IFIs, and acute lymphoblastic leukemia was the predominant underlying malignancy (72.7%). At diagnosis, 81.2% were receiving induction chemotherapy. Prolonged neutropenia occurred in 72.7%, while profound neutropenia was documented in 63.6%. Antifungal prophylaxis was recorded in 69.9%, primarily with itraconazole. Candida spp. (27.3%) and Aspergillus spp. (24.2%) were the leading pathogens; however, filamentous fungi represented 69.7% of cases, including Fusarium spp., Mucorales, dematiaceous fungi, and hyphomycetes (Table 1). The nasosinusal region and oral mucosa were the most frequent sites of infection. Initial treatment commonly involved amphotericin B and voriconazole (48.5%), and 42.4% required surgical intervention. Overall mortality reached 21.2%, with higher rates among yeast infections. Admission to intensive care was the only independent predictor of mortality (OR 35.4, p=0.019, table 2). Conclusion In this cohort, IFIs were closely associated with acute lymphoblastic leukemia, neutropenia, and induction chemotherapy. The pathogen distribution demonstrated both classical agents and a substantial presence of emerging molds. These findings provide new regional data and emphasize the need to strengthen prevention, improve early diagnostic strategies, and optimize antifungal prophylaxis in high-risk pediatric populations.